Multisystem resiliency moderates the major depression–Telomere length association: Findings from the Heart and Soul Study - Puterman, Eli (2013)
Major depressive disorder (MDD) has been associated with reduced leukocyte telomere length (LTL). It is not known, however, whether psychosocial and behavioral protective factors moderate this association. In the current study, we examine whether multisystem resiliency – defined by healthy emotion regulation, strong social connections, and health behaviors (sleep and exercise) – predicts LTL and mitigates previously demonstrated associations between depression diagnosis and LTL. LTL was measured, using a quantitative PCR assay, in 954 patients with stable cardiovascular disease in the Heart and Soul Study. In a fully adjusted model, high multisystem resiliency predicted longer LTL (b = 80.00, SE = 27.17, p = .003), whereas each individual factor did not. Multisystem resiliency significantly moderated the MDD-LTL association (p = .02). Specifically, MDD was significantly related to LTL at 1 SD below the mean of multisystem resiliency (b = −142.86, SE = 56.46, p = .01), but not at 1 SD above the mean (b = 49.07, SE = 74.51, p = .51). This study suggests that MDD associations with biological outcomes should be examined within a psychosocial–behavioral context, because this context shapes the nature of the direct relationship. Further research should explore the cognitive, neural, and other physiological pathways through which multisystem resiliency may confer biological benefit.